A Study on Occupational Health Psychology of Employees in IT Sector in Ahmedabad City (Medico Legal Update, 2020)
In this fast paced global world, human being is surrounded by numerous tensions and various competitors.To survive in this complex world one has to put his whole and sole effort to earn his livelihood. For thishe has to do millions of work which causes stress. So employees need to manage stress and remove theiroccupational illness.The objective of this research is to determine how occupational health psychology is being handled in ITindustry. Along with that I will analyze the importance of stress management from the organizations pointof view, identify reasons, effects and stress release strategies. I have used primary data of the IT industry tostudy how health and safety measures can be taken to remove the mental and physical illness of employeesin IT sector. Secondary data is also used for analysis purpose.